2012
DOI: 10.1039/c2cc34620f
|View full text |Cite
|
Sign up to set email alerts
|

Amine-functionalized zirconium metal–organic framework as efficient visible-light photocatalyst for aerobic organic transformations

Abstract: An amine-functionalized zirconium metal-organic framework (MOF) was used as a visible-light photocatalyst for selective aerobic oxygenation of various organic compounds including alcohols, olefins and cyclic alkanes, at high efficiency and high selectivity. This study shows the great potential for design and application of MOF-based photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
219
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(238 citation statements)
references
References 22 publications
17
219
0
2
Order By: Relevance
“…24,25 The small downeld feature at g ¼ 2.01 is associated with the spatially conned amino-groups in the MOF. 26,41 The EPR spectrum of Co@MOF in the dark (Fig. 8C), with a broad signal around g z 4, is similar to that of high-spin CoBr 2 in CH 3 CN, indicating the presence of residual high-spin Co II impurities (Fig.…”
Section: Mechanistic Aspects Of Hydrogen Evolution Catalysed By Co@momentioning
confidence: 99%
“…24,25 The small downeld feature at g ¼ 2.01 is associated with the spatially conned amino-groups in the MOF. 26,41 The EPR spectrum of Co@MOF in the dark (Fig. 8C), with a broad signal around g z 4, is similar to that of high-spin CoBr 2 in CH 3 CN, indicating the presence of residual high-spin Co II impurities (Fig.…”
Section: Mechanistic Aspects Of Hydrogen Evolution Catalysed By Co@momentioning
confidence: 99%
“…For instance, J. Long et al 68 reported that under visible light irradiation, UiO-66-NH 2 catalyzes the aerobic oxidation of alcohols, olefines and cyclic alkanes. In benzyl alcohol, cyclohexanol and hexyl alcohol oxidation catalysis, 100% selectivity is achieved for these substrates (entry 13, Table 2) , but the conversion rate highly depends on the activation energy of α-C-H bonds.…”
Section: Hydroxylation Of Phenolmentioning
confidence: 99%
“…These studies reveal that the change of organic ligand is an effective method to regulate band gap of MOF. Although in recent years many efforts have been made to modify the organic ligands of MOFs, 5,9,11,20,21 the effects of ligand functionalization on the photocatalytic properties of MOFs are still unclear. It is obvious that a better understanding the mechanism of ligand modification is important to develop new MOF-based photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, many investigations have demonstrated that MOF materials are promising catalysts in photocatalysis. 5,6,[9][10][11][12][13][14][15][16] As one of the most popular MOF, 1,[5][6][7] the titanium-based MIL-125 can catalyze the oxidation of alcohols to aldehydes under the UV irradiation, indicating that MIL-125 is an active photocatalyst. 10 However, because of the large optical band gap (3.6 eV), 10 MIL-125 is only active under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation